Studies of the receptors on melanoma cells for Plasmodium falciparum infected erythrocytes. - Sherwood, J; Roberts, D; Spitalnik, S; Marsh, K; Harvey, E; Miller, L; Howard, R (1989)
We investigated whether thrombospondin plays a role in the binding of Plasmodium falciparum parasitized erythrocytes to C32 melanoma cells. Twelve patient isolates bound variably to melanoma cells, with good correlation between the degree of binding to cells and binding to thrombospondin. With a synchronous preparation of asexual parasites, acquisition of the capacity to bind to thrombospondin occurred at the same parasite stage as binding to melanoma cells. Development of parasites to trophozoites and schizonts correlated with binding of parasitized erythrocytes to thrombospondin and melanoma cells. The infected erythrocyte receptor for thrombospondin was destroyed by mild trypsinization, as was the receptor for melanoma cells. Although these results suggest similarity in the melanoma cell receptor and thrombospondin receptor for infected cells, other results showed that thrombospondin cannot alone be the melanoma cell receptor. Binding to other melanoma cell lines did not correlate with thrombospondin secretion: the RPMI 8252 and G361 cell lines bound few or no infected cells, yet secreted 50-100% as much thrombospondin as C32 cells. Iodinated thrombospondin bound in similar amounts to C32 cells and to noncytoadherent C361 melanoma cells. Binding and nonbinding melanoma cells did not differ in quantity of surface thrombospondin by radioimmunoassay. Thus, although purified, immobilized, thrombospondin binds parasitized erythrocytes, expression of thrombospondin alone on melanoma cells is not sufficient to mediate adherence.